Patterns of relapse in poor-prognosis germ-cell tumours in the GETUG 13 trial: Implications for assessment of brain metastases. (December 2017) - Loriot, Y.; Pagliaro, L.; Fléchon, A.; Mardiak, J.; Geoffrois, L.; Kerbrat, P.; Chevreau, C.; Delva, R.; Rolland, F.; Theodore, C.; Roubaud, G.; Gravis, G.; et al.
Abstract: Background: The GETUG 13 phase III trial tested personalised chemotherapy based on tumour marker decline in patients with poor-prognosis germ-cell tumour (GCT) and demonstrated that a dose-dense regimen improves progression-free survival in patients with an unfavourable decline. We investigated the pattern of relapse for patients included in GETUG 13. Methods: We conducted an analysis of relapse events in patients from GETUG 13. Baseline procedures before inclusion in the trial comprised a thoraco-abdomino-pelvic computed tomography scan and a magnetic resonance imaging of the brain. Results: With a median follow-up of 4.1 years (0.3; 8.8 years), a progression event was observed in 109/254 patients (43%). First event consisted in a marker progression only in 47 patients (43%), a radiographic progression only in 35 patients (32%), a mix progression on both markers and imaging in 12 patients (11%) and death in 15 patients (14%). In patients with radiographic progression only, brain was the predominant site (n = 19/35, 54%). Among patients with unfavourable decline who experienced a radiographic progression (as first and subsequent progression event, n = 58), brain was a site of progression in 28 patients (48%): 12/30 (40%) in patients treated with cisplatin, bleomycin and etoposide and 16/28 (57%) in those treated with dose-dense chemotherapy. Conclusions: Brain metastases develop often, early and frequently as the only site of relapse in the course of poor-prognosis GCT. This raises the question of early detection and optimal treatment of brain metastases in these patients, e.g. by integrating a systematic brain MRI after 2–3 months of chemotherapy. Highlights: The Groupe d'étude des tumeurs urogénitales (GETUG) 13 phase III trial demonstrated that a dose-dense regimen improves progression-free survival in patients with an unfavourable decline. Brain metastases develop often, early, and frequently as the only site of relapse in the course of poor-prognosis GCT. The site of progression may be more likely to be in the brain in patients treated with dose-dense chemotherapy than those treated with BEP Brain was a site of early recurrence in patients whose baseline imaging was negative.